2015
DOI: 10.1093/jxb/erv010
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease J is required for chloroplast and embryo development in Arabidopsis

Abstract: Highlight Arabidopsis RNase J plays an important role in maintaining chloroplast function, and the impairment of chloroplast development in rnj mutants may lead to aberrant embryos with disrupted pattern formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 62 publications
1
29
0
1
Order By: Relevance
“…Moreover, several transcription factors clustered in this group (see Supplementary Table S3 ). Some of them were related to cell and tissue development, such as the orthologs of Arabidopsis LZF1 (probeset Ljwgs_049567.1), BSM (probeset Ljwgs_142668.1), and ATRNJ (probeset Ljwgs_035337.1) that are required for the biogenesis of mitochondria and chloroplasts ( Chang et al , 2008 ; Quesada et al , 2011 ; Chen et al , 2015 ) or the orthologs of Arabidopsis RSM1, AGL62, PIF3, and CDF4 (probesets TM1490.11, chr5.CM0180.16.1, chr5.CM0048.61, and chr4.CM0399.23, respectively) that are involved in the morphogenesis of different plants tissues (see Hamaguchi et al , 2008 ; Roszak and Köhler, 2011 ; Wang et al , 2014 ; Pi et al , 2015 , respectively, for more information on these transcription factors). In addition, some of the transcription factors found in this cluster are involved in the generation of circadian rhythms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several transcription factors clustered in this group (see Supplementary Table S3 ). Some of them were related to cell and tissue development, such as the orthologs of Arabidopsis LZF1 (probeset Ljwgs_049567.1), BSM (probeset Ljwgs_142668.1), and ATRNJ (probeset Ljwgs_035337.1) that are required for the biogenesis of mitochondria and chloroplasts ( Chang et al , 2008 ; Quesada et al , 2011 ; Chen et al , 2015 ) or the orthologs of Arabidopsis RSM1, AGL62, PIF3, and CDF4 (probesets TM1490.11, chr5.CM0180.16.1, chr5.CM0048.61, and chr4.CM0399.23, respectively) that are involved in the morphogenesis of different plants tissues (see Hamaguchi et al , 2008 ; Roszak and Köhler, 2011 ; Wang et al , 2014 ; Pi et al , 2015 , respectively, for more information on these transcription factors). In addition, some of the transcription factors found in this cluster are involved in the generation of circadian rhythms.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the transcription factors identified (probesets Ljwgs_121486.1_at and Ljwgs_035337.1_at) are of particular interest because they are connected to all the photorespiratory genes and primary nitrogen assimilation genes in the co-expression network. The probeset Ljwgs_035337.1_at encodes a transcription factor whose ortholog gene in Arabidopsis (At5g63420) plays a vital role in embryo morphogenesis and apical-basal pattern formation by regulating chloroplast development ( Chen et al , 2015 ), whereas the function of the gene encoded by the probeset Ljwgs_121486.1_at is unknown. The genes encoding both transcription factors were more expressed in plants growing with NH 4 + (cluster 4 from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis null mutants for RNase J are embryo-lethal, displaying albino ovules containing aborted embryos [63]. Further examination suggested that RNase J is required for the organization and functioning of the shoot apical meristems, cotyledons, and hypocotyls [64]. In addition, the transport and response of auxin was impaired [64].…”
Section: Consequences Of Removing or Down-regulating Rnase J In Plantsmentioning
confidence: 99%
“…Further examination suggested that RNase J is required for the organization and functioning of the shoot apical meristems, cotyledons, and hypocotyls [64]. In addition, the transport and response of auxin was impaired [64]. Why the absence of RNase J activity results in embryo lethality is still obscure; however, the importance of plastid gene expression for embryo maturation in plants is well documented [65,66].…”
Section: Consequences Of Removing or Down-regulating Rnase J In Plantsmentioning
confidence: 99%
See 1 more Smart Citation